On differential subordinations for a class of analytic functions defined by a linear operator. (9th September 2004) - Ravichandran, V.; Silverman, Herb; Kumar, S. Sivaprasad; Subramanian, K. G.
Abstract : We obtain several results concerning the differential subordination between analytic functions and a linear operator defined for a certain family of analytic functions which are introduced here by means of these linear operators. Also, some special cases are considered.